ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII DALAM MATERI SEGITIGA - Kodongan, Gidieon Romario; Regar, Vivian E; Mangobi, James U (SOSCIED, 2025)
The aim of this study was to assess students' understanding of mathematical concepts pertaining to triangle topics. This research employed a qualitative approach, intending to generate descriptive data through written and verbal expressions from various sources observed. The study took place at SMP Negeri 1 Tenga, located in South Minahasa. Data collection methods comprised written tests and interviews, which were administered to a total of 12 eighth-grade students. The gathered data was analyzed by categorizing students into three groups based on their understanding of mathematical concepts. Findings revealed that 83.3% of the eighth-grade students at SMP Negeri 1 Tenga achieved a high level of understanding at the translation stage, as this indicator was relatively straightforward. In contrast, 66.6% demonstrated a good understanding at the interpolation stage, as some students were able to effectively select and apply appropriate procedures. However, only 33.3% of students exhibited comprehension at the extrapolation level, which fell into the low category, primarily due to difficulties in problem-solving accuracy and an insufficient grasp of the problems. Additionally, the distribution of understanding levels included 3 students in the high category, 3 in the medium category, and 6 who displayed a very low understanding of mathematical concepts at both the extrapolation and interpolation levels, as well as at the translation level